Quels critères pour une artistique du geste et du numérique ordinaires ? - Alice Dupas (Cahiers de Narratologie)
Within pragmatist aesthetics, a pragmatist aesthetics of experience argues that everything, even the most ordinary banality, can becomes aesthetic under the impulse of the person bearing the experience. The boundless aestheticization thus induced can lead to an artialization that is itself unlimited, which makes everything art through the prism of the sensitive experience of the person receiving the work of art. It would seem, however, that in its active, embodied encounter with the work, the person actualizes objective properties rather than produces them. This approach makes it possible to distinguish between art and ordinary life based on the work’s objective technical and informational conditions, without neglecting to value the person’s active experience which takes place primarily through its body. It also enables to distinguish, in the current digital age, between a certain form of digital art that meets these conditions, on the one hand, and what can be described as ordinary digital art, on the other.